2018
DOI: 10.19084/rca18002
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Panicum genotypes submitted to periods of cessation of irrigation

Abstract: This study aimed to evaluate the morphological characteristics of Panicum maximum clones during the regrowth period following cessation of irrigation. Panicum clones were collected in Sergipe and in three Pernambuco locations ('São Bento do Una', 'Itambé' and 'São João da Coroa Grande'), in addition to 'Mombaça', 'Tanzânia' and 'Massai' cultivars. The treatments consisted of seven clones, which were subjected to either 7, 14, 21 or 28 days of water suspension. The experimental design was completely randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For plants subjected to water deficit conditions, DMDM production was lower. Lima et al (2018), evaluating the morphological characteristics of M. maximus clones during the regrowth period, after the interruption of irrigation, reported that after one and three weeks there was a tendency to decrease the number of dead leaves. The highest DMDM production was for plants subjected to irrigated soil up to 100% field capacity (1.47 g pot -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For plants subjected to water deficit conditions, DMDM production was lower. Lima et al (2018), evaluating the morphological characteristics of M. maximus clones during the regrowth period, after the interruption of irrigation, reported that after one and three weeks there was a tendency to decrease the number of dead leaves. The highest DMDM production was for plants subjected to irrigated soil up to 100% field capacity (1.47 g pot -1 ).…”
Section: Resultsmentioning
confidence: 99%